Validity of Click-Wrap and Browse-Wrap Agreements in the Indonesian Agreement Legal System - Arief, Anggreany; Muhdar, Muh. Zulkifli (PT. Riset Press International, 2025)
The growth of electronic transactions in Indonesia has led to the emergence of various forms of digital agreements, including click-wrap agreements and browse-wrap agreements. Both types of agreements have become common legal instruments on digital platforms; However, their validity within Indonesia's contract law system remains a subject of academic and practical debate. This study aims to analyze the validity of click-wrap agreements and browse-wrap agreements in light of Article 1320 of the Civil Code, Law Number 11 of 2008 on Electronic Information and Transactions (EIT Law) and its amendments, and Law Number 8 of 1999 on Consumer Protection. The research employs a normative legal method using a statute approach and a comparative approach. The findings indicate that click-wrap agreements possess stronger legal force than browse-wrap agreements due to the explicit expression of user consent. Browse-wrap agreements occupy a legally vulnerable position because they do not adequately satisfy the element of mutual consent as required by Article 1320 of the Civil Code. This study recommends the establishment of more specific regulations governing minimum standards for digital agreements in Indonesia to provide legal certainty for businesses and consumers.